Обзор криптографических систем в группах кос - Горбенко, И. Д.; Паршина, Д. А. (ХНУРЭ, 2011)
The past several years have seen an explosion of interest in the cryptographic applications of non-commutative braid groups in particular are especially desirable, as they provide difficult computational problems and can be implemented quite efficiently. Several different groups of researches have proposed numerous cryptographic protocols that make use of braid groups. This expository paper discusses the specifications and responses of both the M.Anshel,I.Anshel, and Goldfeld Commutator and the Co et al. Diffie-Hellman Conjugacy key exchange protocols.
Keywords: криптографические приложения; некоммутативные группы